Knowledge Transfer between University and Industry: Development of a Vision Measuring System - Figueiredo, Joao (2013)
This chapter approaches the transfer of knowledge between University and Industry which potentiates great benefits for both partners in designing innovative solutions, in the optimal allocation of resources, in motivating the students for new challenging tasks and finally in integrating multidisciplinary teams University/Industry. The case study here presented is related to the field of industrial maintenance, concerning the measuring and monitoring of the railroad wheel profiles in the Portuguese railway company, CP - Comboios Portugal. A vision system to measure the wearing of the wheels of a train moving at a slow speed of 5Km/h is here studied. A 1:1 scale static prototype is developed and the calibration and testing procedures are presented. The developed prototype is based on an image processing system to provide for the automatic measurement of the moving wheels. The wheel’s profile is acquired by the illumination of the wheel through a secant horizontal light plane. The profile’s image is processed by identifying the line of the greatest light gradient in the whole image. The gradient’s profile is then converted to the wheel’s radial profile by means of a coordinate transformation model, which transforms the image plane into the wheel’s radial plane. Experimental results are presented and discussed.